Schizophrenia spectrum participants have reduced visual contrast sensitivity to chromatic (red/green) and luminance (light/dark) stimuli: new insights into information processing, visual channel function, and antipsychotic effects - Cadenhead, Kristin S.; Dobkins, Karen; McGovern, Jessica; Shafer, Kathleen (Frontiers in Psychology, 2013)
Background: Individuals with schizophrenia spectrum diagnoses have deficient visual information processing as assessed by a variety of paradigms including visual backward masking, motion perception and visual contrast sensitivity (VCS). In the present study, the VCS paradigm was used to investigate potential differences in magnocellular (M) vs. parvocellular (P) channel function that might account for the observed information processing deficits of schizophrenia spectrum patients. Specifically, VCS for near threshold luminance (black/white) stimuli is known to be governed primarily by the M channel, while VCS for near threshold chromatic (red/green) stimuli is governed by the P channel. Methods: VCS for luminance and chromatic stimuli (counterphase-reversing sinusoidal gratings, 1.22 c/degree, 8.3 Hz) was assessed in 53 patients with schizophrenia (including 5 off antipsychotic medication), 22 individuals diagnosed with schizotypal personality disorder and 53 healthy comparison subjects. Results: Schizophrenia spectrum groups demonstrated reduced VCS in both conditions relative to normals, and there was no significant group by condition interaction effect. Post-hoc analyses suggest that it was the patients with schizophrenia on antipsychotic medication as well as SPD participants who accounted for the deficits in the luminance condition. Conclusions: These results demonstrate visual information processing deficits in schizophrenia spectrum populations but do not support the notion of selective abnormalities in the function of subcortical channels as suggested by previous studies. Further work is needed in a longitudinal design to further assess VCS as a vulnerability marker for psychosis as well as the effect of antipsychotic agents on performance in schizophrenia spectrum populations.